The Role and Applications of Forensic Accounting: A Study on Its General Idea in India: Examining the role and applications of forensic accounting in addressing misconduct and fraud in India's industrial sector (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Since theft is particularly heinous malfeasance in India, the involvement of forensic accountants has come to light particularly due to the increasing incidence of misconduct and white-collar crimes in the country’s economic sector. This has been found that, on average, 8.5 percent of the wealth earned by the countries many industries such as the life insurance industry is responsible for fraud losses annually. Perhaps the first case of misconduct in the countries Industrial sector was identified in the context of SBI Life for breaching the regulatory standards for protecting the interests of insurers and maintaining effective internal controls. uIn this context, the study attempts to examine potential irregularities in the Indian Industrial sector over ten years from 2011 to 2017. For this purpose, the study will analyze the Role and Applications of Forensic Accounting to verify the consistency of the Information observed.